PRZEFORMUŁOWANIE W PRZYSWAJANIU I UCZENIU SIĘ JĘZYKÓW: SPECYFIKA I FUNKCJE ODTWARZANIA OPOWIADANIA - Karpińska-Szaj, Katarzyna; Wojciechowska, Berbadeta (Neofilolog, 2018)
This article is about a task which required learners to reformulate a story which they had listened to in writing. In the context of foreign language learning, the original text provides a discourse model, whereas the way it is rephrased reflects students’ skill to use the new information in their own words. Retelling can also be treated as language practice focused on learning and practising new vocabulary and sentence structures. The research concentrated on fragments of text that were an extension of the original text that was retold by an elementary group of students of French philology (A2 level according to The Common European Framework of Reference for Languages, 2003) in Polish and French (the foreign language). Comparison of speech produced in the two languages made it possible to consider the nature and function of the learners’ discourse competence which, depending on the students’ personal goals and communicative experience, differed in the two cases. The data collected can serve as a starting point for planning further steps to develop students’ metadiscoursal awareness with the use of the retelling of a story as a learning strategy.